2013
DOI: 10.1007/s13197-013-1189-2
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activities and phenolic contents of three red seaweeds (Division: Rhodophyta) harvested from the Gulf of Mannar of Peninsular India

Abstract: The antioxidant activities of methanol extract and its solvent fractions (n -hexane, dichloromethane and ethyl acetate) of three red seaweeds (Hypnea musciformis , H. valentiae , and Jania rubens ) collected from the Gulf of Mannar of South eastern coast of India were evaluated, using different in vitro systems, viz., DPPH, ABTS, HO radical scavenging activities, H 2 O 2 scavenging ability, Fe 2+ ion chelating ability and reducing potential. Folin-Ciocalteu method was used to determine the total phenolic conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
68
4
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 110 publications
(81 citation statements)
references
References 29 publications
6
68
4
1
Order By: Relevance
“…In addition, methanol extract showed the presence of terpenoid which may for the increased antioxidant activity be compared to other extracts. Similar findings were also reported by Chang and Lin, , whereas Chakraborty et al () reported that methanol extract and its ethyl acetate fractions of Indian originated H. musciformis showed higher antioxidant activity compared to the present study. These differences might be due to the origin of seaweed and the choice of solvent fractions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, methanol extract showed the presence of terpenoid which may for the increased antioxidant activity be compared to other extracts. Similar findings were also reported by Chang and Lin, , whereas Chakraborty et al () reported that methanol extract and its ethyl acetate fractions of Indian originated H. musciformis showed higher antioxidant activity compared to the present study. These differences might be due to the origin of seaweed and the choice of solvent fractions.…”
Section: Discussionsupporting
confidence: 92%
“… and Chakraborty et al . ). However, Bangladeshi seaweed as a source of antioxidant has not been determined and reports on antioxidant and DNA protection activities of H. musciformis are limited.…”
Section: Introductionmentioning
confidence: 97%
“…Although Acanthophora spicifera had low phenolic content, its extract had significant antioxidant activity. This is likely because this species belongs to the red algae family Rhodomelaceae that is rich in bromophenols, sharing one or several benzene rings, where the hydroxyl groups are substituted by a bromine group with potent antioxidant activities (Liu et al 2011;Chakraborty et al 2015). Other abundant compounds in A. spicifera are sulfated polysaccharides such as agaran, which possibly were co-extracted and might also support its antioxidant activity (Ganesan et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, FM4 was purified and characterized by marine algae. This is due to the presence of oligosaccharides, glycolipids, phenolic compounds and small molecular weight bioactive compounds and their effect was proved in experimental animals [13,14]. Marine algae produce a wide range of new secondary metabolites with various biological activities which may have potential applicability in the field of pharmaceutical industry to provide a stable platform for medicine industries [15].…”
Section: Methodsmentioning
confidence: 99%